Exclusion as urban policy: The Dutch 'Act on Extraordinary Measures for Urban Problems'. (August 2018) - van Gent, Wouter; Hochstenbach, Cody; Uitermark, Justus
The Dutch government introduced the Act on Extraordinary Measures for Urban Problems in 2006 to bolster local regeneration efforts. The act enables local governments to stop specific groups of deprived households from moving into designated neighbourhoods. More specifically, the Act allows local governments to refuse a residence permit to persons who have lived in the metropolitan region for less than six years and who do not receive an income from work, pensions or student loans. The policy is based on the idea that reducing the influx of poor newcomers improves liveability by providing a temporary relief of the demand for public services and by making neighbourhoods demographically 'balanced' or 'socially mixed'. This review examines the socio-spatial effects of the Act in Rotterdam between 2006 and 2013. While the Act produces socio-demographic changes, the state of the living environment in designated areas seems to be worsening rather than improving. Our findings show that the policy restricts the rights of excluded groups without demonstrably improving safety or liveability. The review concludes with a reflection on how the Act may signify a broader change in European statecraft and urban policy.